A nucleic acid labeling chemistry reveals surface DNA on exosomes - Filip Bošković; Priyanka Dutta Gupta; Jian Zhang; Yamuna Krishnan; Jack W. Szostak (Proceedings of the National Academy of Sciences, 2026)
Chemical labeling of nucleic acids is essential to pinpoint the structure, localization, and function of RNA and DNA. Yet, reversible sequence-independent chemistries that can label native RNA and DNA remain poorly developed. Here, we describe Reversible Uridine Nitrilium-mediated Addition (RUNA), a reversible covalent chemistry that selectively modifies uridine and thymidine residues via N3 deprotonation and reaction with a nitrilium ion intermediate generated from an aldehyde and an isonitrile. The reaction forms a stable N3 adduct that can be quantitatively reversed by hydrolysis. By using reagents that are either membrane permeable or impermeable, we demonstrate the localization and function of DNA on exosomes. Although exosomes harbor nucleic acids, whether the latter are encapsulated in the exosome lumen or are surface-adhered is unknown. RUNA revealed that exosomes display DNA on their outer surface. The abundance of such surface DNA increases upon DNA-damage accumulation in cancer cells that are treated with a PARP inhibitor. This surface DNA drives exosome uptake by M2-polarized macrophages through scavenger receptors and triggers a shift toward an M1-like proinflammatory state. The selective labeling of surface DNA revealed an unexpected mechanism by which exosomes engage innate immune cells. RUNA is a versatile tool to analyze the nucleic acid content and functionality of extracellular vesicles in health and disease.